The Decision-Making Process for the Selection of Naval Base VI to Uphold its Functions Through the Multi-Criteria Decision Making (MCDM) Integration Approach - Siregar, Rudi Hartono; Surbakti, Udi; Prasutiyon, Hadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research discusses the degradation condition of Naval Main Bases VI Makassar, which has experienced a decline in function as a naval operational support center. Factors such as the impact of the Makassar New Port (MNP) reclamation project and the morphological condition of the area have influenced the optimal implementation of base duties and the decrease in the base's confidentiality as an Integrated Fleet Weapon System (SSAT). Through the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method, this research aims to determine the best alternative in choosing the location of Naval Main Bases VI. The alternatives involved are Naval Bases Mamuju, Kendari, Naval Base Baubau, and Naval Base Palu. Criteria and sub-criteria, attributes as the basis for determining the best alternative choices include geography, resources, socio-cultural aspects, and vulnerability. The research results show that the use of the MOORA method provides optimal risk mitigation decisions for selecting the best alternative location. This research serves as an objective recommendation when deciding on more effective and targeted decision-making, thus using this method can achieve optimal results and can further develop knowledge in Decision Support Systems (DSS). The calculation results with the highest ranking are: Naval Base Palu with a value of (0.2402); this method is suitable for selecting the Alternative Naval Main Bases VI that is acceptable